PENERAPAN MEDIA MONOPOLI UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR IPA DENGAN MODEL KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) DI KELAS IV SDN 60/II MUARA BUNGO - zi, fauziah; Maulana, Ikhsan; Isnaini, Annisa (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2021)
The design of this study was classroom action research through the Cooperative model type. The application of monopoly media to improve the science learning process and outcomes with the cooperative model team games toornament (TGT) type in class IV SDN 60 / II Muara Bungo, Rimbo sub-district, Bungo district, used two cycles, each cycle consists of four stages, namely planning, implementation, observation and reflection. The research subjects were the teacher (researcher) and class students in class IV SDN 60 / II Muara Bungo Data collection techniques using observation and tests. The results showed that: (1) teacher performance assessment in the first cycle of meeting I obtained a score of 68,75% with good criteria, meeting II with a score of 75% with good criteria. In the second cycle meeting I obtained a score of 81,25% with good criteria, and meeting II with a score of 87,5% criteria was very good. (2) The classical completeness of the learning outcomes of the students in the first cycle of the first meeting was 70% and the second cycle in the second meeting was 75%. In cycle II meeting I was 85% and meeting II was 90%.